Advantages, Challenges and New Frontiers in Using Information Communication Technologies in Societal and Social Movement Research - Mayo Fuster Morell (tripleC: Communication, Capitalism & Critique)
This paper includes a review of the main methodological trends and methods related to ICTs adopted in social movement research. It then reflects on the advantages and challenges of using ICTs for research. Finally, it suggests potential and new frontiers in the use of ICTs for research.